Effectiveness of an Activity Based Learning on Attitude of Students towards Education for Sustainable Development - Kaur, Jagpreet; Sandhu, Khushgeet Kaur (SCHOOL SCIENCE, 2021)
The aim of this study was to investigate the effect of activity-based learning on the attitude of students towards education for sustainable development. The present study was quasi-experimental in nature, conducted with the help of pre-test and post-test control group design. There were 99 participants in this study, with experimental and control groups comprising 50 and 49 students respectively. While the experimental group was taught with the help of activity-based learning, the control group learnt with the help of traditional method of teaching for the duration of four weeks. Attitude towards Education for Sustainable Development Scale was used as pre-test and post-test. The findings suggested that the activity-based learning given to the experimental group had a significantly positive effect on the attitude of students towards education for sustainable development.